Gender Based Violence Among Pregnant Women: A Hospital Based Study - Chaudhary, Shrawan Kumar; Chaudhary, Pushpa (Journal of Nepalgunj Medical College, 2017)
Introduction: Gender Based Violence (GBV) is prevalent and exists to some extent in virtually all societies throughout the world. Evidence shows consistent negative effect of violence on health of women particularly. This hidden disease is perceived as a social issue and not a health issue and is often overlooked by health care providers. Methodology: This study was a Cross Sectional descriptive study conducted at national Academy of Medical Science affiliated Paropaker Women's and Maternity Hospital, Kathmandu enrolling 950 pregnant women from the emergency admission room who were interviewed using structured questionnaire from mid march to the end August in the year 2007. Result and discussion: Among 950 women suffered from gender based violence (33.36%). One hundred and fifty women faced psychological violence (47.31%), seventy two clients faced physical violence (22.71%), and forty two women faced sexual violence (13.24%) and rest of them faced all types of violence. Violence was reported during the current pregnancy (41.32%). Husbands were perpetrator of violence for almost on third of women (34.06%), followed by mother in low (18.29%). Joint violence by family members was quit common (28.1%). Perpetrator outside family was responsible for approximately 20% of cases. Domestic violence was extremely common accounting for more than four fifty of cases (81.38%). Among sexual violence, (45.45%) women were victim of marital rape. Alcoholism as one of the common reason for wife battering, observed in this study in Maternity Hospital which is still prevalent in Nepal. Often, verbal abuse is an excuse for imposing discipline in the family. Women's economic and emotional dependence on husband could be responsible for the vulnerable status in family. Health seeking behavior following violence was found to be extremely low in this study suggestion gender based violence as a privet matter.